Smartphone‐Delivered MBRP and Quality of Life among Individuals With Opioid Use Disorder: A Pilot Before–After Study - Shadi Dashtbani; Hadi Ramesh; Narges Norouzkhani; Ali Saghebi; Atefeh Khoshkangin; Mohammad Reza Mazaheri Habibi (Health Science Reports, 2026)
ABSTRACT Background Mindfulness‐Based Relapse Prevention (MBRP) combines mindfulness practice with relapse‐prevention strategies and has demonstrated efficacy in improving psychological well‐being among individuals with substance use disorders. This pilot study evaluated quality‐of‐life changes following an audio‐based mobile MBRP application delivered as an adjunct to methadone maintenance treatment (MMT) among individuals with opioid use disorder (OUD). Materials and Methods This single‐arm before–after study included 14 male participants with OUD receiving MMT at two addiction treatment clinics. Participants used the MBRP application for 8 weeks alongside routine care. Quality of life was assessed using the SF‐36 at baseline, post‐intervention, and 3‐month follow‐up. Session completion was monitored through weekly clinician‐verified contacts. Substance use and relapse status were monitored descriptively as secondary clinical indicators. Results Mean SF‐36 scores increased from 40.34 ± 11.26 at baseline to 66.57 ± 13.39 post‐intervention and remained above baseline at follow‐up (57.76 ± 10.89). Significant improvements were observed from baseline to post‐intervention (mean difference = 26.23, 95% CI: 17.73–34.73, p < 0.001, Cohen's d z = 1.78) and from baseline to follow‐up (mean difference = 17.42, 95% CI: 11.84–22.99, p < 0.001, Cohen's d z = 1.80). Session‐completion rate was 92.9% (mean = 7.43 sessions per participant). At follow‐up, 11 participants (78.6%) remained free of documented illicit opioid use; three (21.4%) had documented relapse events, reported descriptively given the uncontrolled design. Conclusion Participation in the mobile MBRP application was associated with quality‐of‐life improvements remaining above baseline at 3‐month follow‐up, supporting feasibility in routine addiction‐treatment settings. Randomized controlled trials with addiction‐specific outcomes, standardized acceptability instruments, and objective engagement analytics are needed to establish effectiveness.